Chronic Pain and Grief (2019)
Introduction: The aim of this article was to conduct a systematic review in order to find information that enables a connection between chronic pain and the grieving process to be established, beyond the intuitive relationships that connects them. Methods: The medical literature was reviewed in search of articles that provide some evidence of the connection between chronic pain and grief. Results: The available information on both topics by themselves is profuse but there are very few publications that deal with both issues simultaneously. Conclusions: The connection between chronic pain and grief has been mentioned intuitively as a condition taken for granted. However, little evidence of this relationship has been published, which suggests that this topic has not been widely researched. © 2017 Asociación Colombiana de Psiquiatría